“My journey map”: Developing a qualitative approach to mapping young people’s progress in residential rehabilitation - Roarty, Lynn; Wildy, H.; Saggers, Sherry; Conigrave, K.; Wilson, Amanda; Di Nicola, K.; Webb, J.; Faulkner, J. (Federal Legal Publications, Inc, 2012)
Young people with substance misuse issues are at risk of harm from significant negative health and life events. Contemporary research notes both a historical failure to recognize the unique needs of adolescents, and the ongoing need for dedicated adolescent treatment programs and outcome measures. It is concerning that there is so little literature assessing the quality, availability, and effectiveness of adolescent-focused treatment programs, and no adolescent-specific measurement tools centered on a young person’s progress in residential treatment. This article reports on the process of developing a qualitative approach to mapping progress in treatment over time. The research seeks to develop an approach that captures, at three points in time and from multiple viewpoints, the progress of young people in four residential rehabilitation services located in New South Wales and Western Australia, across several dimensions of the personal and social aspects of life. Our aim is to develop an approach that is accessible to the alcohol and other drug workforce, and that informs the development of a psychometrically robust quantitative measure of progress that is meaningful and useful both to practitioners and to the young people themselves.